Feasibility and Timing of Cytoreduction Surgery in Advanced (Metastatic or Recurrent) Gastrointestinal Stromal Tumors During the Era of Imatinib. Issue 24 (June 2015) - Chang, Shih-Chun; Liao, Chien-Hung; Wang, Shang-Yu; Tsai, Chun-Yi; Chiang, Kun-Chun; Cheng, Chi-Tung; Yeh, Ta-Sen; Chen, Yen-Yang; MA, Ming-Chun; Liu, Chien-Ting; Yeh, Chun-Nan; Merrett., Neil
<x xml:space="preserve">Abstract</x> Abstract The prognosis of advanced gastrointestinal stromal tumors (GISTs) was dramatically improved in the era of imatinib. Cytoreduction surgery was advocated as an additional treatment for advanced GISTs, especially when patients having poor response to imatinib or developing resistance to it. However, the efficacy and benefit of cytoreduction were still controversial. Likewise, the sequence between cytoreduction surgery and imatinib still need evaluation. In this study, we tried to assess the feasibility and efficiency of cytoreduction in advanced GISTs. Furthermore, we analyzed the impact of timing of the cytoreduction surgery on the prognosis of advanced GISTs. We conducted a prospective collecting retrospective review of patients with advanced GISTs (metastatic, unresectable, and recurrent GISTs) treated in Chang Gung memorial hospital (CGMH) since 2001 to 2013. We analyzed the impact of cytoreduction surgery to response to imatinib, progression-free survival (PFS), and overall survival (OS) in patients with advanced GISTs. Moreover, by the timing of cytoreduction to imatinib, we divided the surgical patients who had surgery before imatinib use into early group and those who had surgery after imatinib into late. We compared the clinical response to imatinib, PFS and OS between early and late cytoreduction surgical groups. Totally, 182 patients were enrolled into this study. Seventy-six patients underwent cytoreduction surgery. The demographic characteristics and tumor presentation were similar between surgical and non-surgical groups. The surgical group showed better complete response rate (P < 0.001) and partial response rate (P = 0.008) than non-surgical group. The 1-year, 3-year, and 5-year PFS were significantly superior in surgical group (P = 0.003). The 1-year, 3-year, and 5-year OS were superior in surgical group, but without statistical significance (P = 0.088). Dividing by cytoreduction surgical timing, the demographic characteristics and tumor presentation were comparable in early and late groups. The late cytoreduction group presented higher R0 resection rate (59.1% vs 31.5%, P = 0.025). However, the PFS and OS were comparable in both groups. Combining imatinib with cytoreduction increased the response rate to imatinib and prolonged PFS in patients with advanced GISTs. Moreover, early and late cytoreduction surgery was comparable in prognosis, although late cytoreduction revealed higher complete resection rate.